Global burden of anemia and cause among children under five years 1990–2019: findings from the global burden of disease study 2019 - Liu, Yujuan; Ren, Weifang; Wang, Shuying; Xiang, Minmin; Zhang, Shunxian; Zhang, Feng (Frontiers in Nutrition, 2024)
Background: Anemia represents a significant global health issue affecting numerous children and women, characterized by diminished hemoglobin levels that may impede cognitive and developmental progress. Although commonly attributed to iron deficiency, the etiology of anemia in this demographic is multifaceted, encompassing nutritional, genetic, and infectious contributors. Nonetheless, there is a lack of highquality data on anemia prevalence and causes analysis among children under five years.The aim of this study was to provide a comprehensive global assessment of the burden of anemia and its causes among children under five years, using data from the Global Burden of Disease Study 2019.Methods: This investigation utilized data from the Global Burden of Disease Study (GBD) 2019 to assess the prevalence and years lived with disability (YLD) attributable to anemia in children under five from 1990 to 2019. Analyses were conducted to delineate age-specific YLD, prevalence rates, and etiological factors, with stratification by gender and Socio-Demographic Index (SDI).